Adolescents’ health and wellbeing: Trends and insights from the National Family Health Surveys, 2006, 2016, and 2021 - Pant, Anjali; Patwardhan, Sharvari; Nguyen, Phuong Hong; Scott, Samuel P.; Avula, Rasmi; Hemalatha, R.; Singh, S. K.; Chamois, Sylvie; Menon, Purnima (International Food Policy Research Institute, 2023)
South Asia is home to more adolescents than any global region, and one in five adolescents globally live in India. Among the many issues that adolescents face, poor nutrition, non-communicable diseases (NCDs), marriage, and childbearing are of key importance as they have far-ranging and intergenerational consequences. This Data Note examines the national-level trends and spatial variability at state and district levels for a set of key nutrition outcomes, NCDs, marriage, and childbearing status among Indian adolescents (15-19 years; girls and boys). The findings are based on data from the three rounds of India’s National Family Health Surveys (NFHS) – NFHS 2006, 2016, and 2021. The Data Note concludes with key takeaways for adolescents’ wellbeing and identifies areas for improvement. This Data Note can be used for further inquiry by stakeholders including researchers, policymakers, and program staff at multiple levels.